Decentering Music: A Critique of Contemporary Musical Research - Korsyn, Kevin Ernest (Oxford Oxford University, 2003)
As a work of cultural criticism that recalls the concerns of Foucault, Hayden White, Zizek, and others Decentering Music examines the struggle for the authority to speak about music at a time when the humanities are in crisis. By linking the institutions that support musical research, including professional associations and universities, to complex historical changes such as globalization and the commodification of knowledge, Korsyn undertakes a critique of musical scholarship as an institutional discourse, while contributing to a general theory of disciplinary structures that goes beyond the limits of any single field.In asking a number of fundamental questions about the models through which disciplinary objects in music are constructed, Korsyn suggests unexpected relationships between works of musical scholarship and the cultural networks in which they participate. Thus David Lewin's theory of musical perceptions is compared to Richard Rorty's concept of the "liberal ironist," Susan McClary's feminist narrative of music history is juxtaposed with T.S. Eliot's "dissociation of sensibility," and Steven Feld's work in recording the music of the Kaluli people is compared to the treatment of ambient sound in contemporary cinema.Developing a framework for interpretation in dialogue with a number of poststructuralist writers, Korsyn goes far beyond applying their thought to the analysis of music; by showing the cultural dilemmas to which their work responds, Korsyn suggests how musical research already participates in these ideas. Rather than impose any single method, Decentering Music empowers readers to choose for themselves by interrogating their own values and ideological commitments, exploring the enabling conditions for statements about music. By demonstrating the complicity of opposing positions and challenging readers to reexamine their own values, Decentering Music will surely provoke debate, while appealing to readers in a variety of fields, and to anyone concerned about the crisis in the humanities.
Keywords: Artistic research; Music philosophy and esthetics